Activation of AMPK/mTOR-Driven Autophagy and Suppression of the HMGB1/TLR4 Pathway with Pentoxifylline Attenuates Doxorubicin-Induced Hepatic Injury in Rats - Hany H. Arab; Ahmed H. Eid; Shuruq E. Alsufyani; Ahmed M. Ashour; Alwaleed M. Alnefaie; Nasser M. Alsharif; Abdullah M. Alshehri; Abdulmajeed A. Almalawi; Abdulmajeed A. Alsowat; Hayat A. Abd El Aal; Eman S. G. Hassan; Wessam H. Elesawy; et al. (MDPI AG, 2024)
Despite being an effective chemotherapeutic agent, the clinical use of doxorubicin (DOX) is limited by several organ toxicities including hepatic injury. Pentoxifylline (PTX) is a methylxanthine derivative with marked anti-inflammatory and anti-apoptotic features. It is unknown, however, whether PTX can mitigate DOX-evoked hepatotoxicity. This study aims to explore the potential hepatoprotective impact of PTX in DOX-induced hepatic injury and the underlying molecular mechanisms. Histopathology, immunohistochemistry, and ELISA were used to examine liver tissues. The current findings revealed that PTX administration to DOX-intoxicated rats mitigated the pathological manifestations of hepatic injury, reduced microscopical damage scores, and improved serum ALT and AST markers, revealing restored hepatic cellular integrity. These favorable effects were attributed to PTX's ability to mitigate inflammation by reducing hepatic IL-1β and TNF-α levels and suppressing the pro-inflammatory HMGB1/TLR4/NF-κB axis. Moreover, PTX curtailed the hepatic apoptotic abnormalities by suppressing caspase 3 activity and lowering the Bax/Bcl-2 ratio. In tandem, PTX improved the defective autophagy events by lowering hepatic SQSTM-1/p62 accumulation and enhancing the AMPK/mTOR pathway, favoring autophagy and hepatic cell preservation. Together, for the first time, our findings demonstrate the ameliorative effect of PTX against DOX-evoked hepatotoxicity by dampening the hepatic HMGB1/TLR4/NF-κB pro-inflammatory axis and augmenting hepatic AMPK/mTOR-driven autophagy. Thus, PTX could be utilized as an adjunct agent with DOX regimens to mitigate DOX-induced hepatic injury.